When Does Stress Help or Harm? The Effects of Stress Controllability and Subjective Stress Response on Stroop Performance - Henderson, Roselinde K.; Snyder, Hannah R.; Gupta, Tina; Banich, Marie T. (Frontiers in Psychology, 2012)
The ability to engage in goal-directed behavior despite exposure to stress is critical to resilience. Questions of how stress can impair or improve behavioral functioning are important in diverse settings, from athletic competitions to academic testing to clinical therapy. Previous research suggests that controllability is a key factor in the impact of stress on behavior: learning how to control stressors buffers people from the negative effects of stress on subsequent cognitively demanding tasks. In addition, research suggests that the impact of stress on cognitive functioning depends on an individual’s response to stressors: moderate responses to stress can lead to improved performance while extreme (high or low) responses can lead to impaired performance. The present studies tested the hypothesis that 1) learning to behaviorally control stressors leads to improved performance on a test of general executive functioning, the color-word Stroop, and that 2) this improvement emerges specifically for people who report moderate (subjective) responses to stress. Experiment 1: Stroop performance, measured before and after a stress manipulation, was compared across groups of undergraduate participants (n=109). People who learned to control a noise stressor and received accurate performance feedback demonstrated reduced Stroop interference compared with people exposed to uncontrollable noise stress and feedback indicating an exaggerated rate of failure. In the group who learned behavioral control, those who reported moderate levels of stress showed the greatest reduction in Stroop interference. In contrast, in the group exposed to uncontrollable events, self-reported stress failed to predict performance. Experiment 2: In a second sample (n=90), we specifically investigated the role of controllability by keeping the rate of failure feedback constant across groups. In the group who learned behavioral control, those who reported moderate levels of stress showed the gre